Landing wise program: feasibility study protocol for Parkinson’s disease - Fernandes, Júlio Belo; Domingos, Josefa; Família, Carlos; Santos, Cátia; Santana, Diana; Gregório, Francisco; Costa, Inês; Afonso, Joana; Matos, Lúcia; Marques, Solange; Santos, Tânia; Fernandes, Sónia; et al. (Frontiers in Medicine, 2023)
Regardless of the benefits of fall prevention programs, people with Parkinson's disease (PD) will still fall. Therefore, it is crucial to explore novel therapeutic approaches that are well-accepted and effective for addressing fall risk and the fear of falls among this population. The present study aims to assess the feasibility of the Landing Wise program as a therapeutic intervention for reducing the fear of falling in people with PD. A mixed-methods study will be conducted using convenience sampling to recruit 20 people with PD with a moderate concern of falling from a Parkinson's Patients Association. In addition to usual care, participants will attend two days per week, 90 minutes group sessions for eight weeks. The intervention combines group cognitive behavioral intervention with the training of safe landing strategies. Feasibility will be assessed by six key domains (recruitment strategy and rates, enrollment, retention, acceptability, reasons for decline/withdrawal, and adverse events). Quantitative data will be analyzed using descriptive statistics to characterize the sample, followed by inferential statistics to evaluate differences in the Short Falls Efficacy Scale-International Scale, Movement Disorder Society Unified Parkinson's Disease Rating Scale, Timed Up Go, 6-Minutes Walking Distance, and fall frequency and severity scores between baseline and final assessment. Qualitative data will be analyzed using an inductive thematic analysis process. There is a growing interest in developing new effective therapeutic approaches for people with PD. If proven program feasibility, this study precedes a randomized controlled trial to establish the effectiveness of the Landing Wise program.